"We Need to Feel Safe": Experiences of Gifted LGBTQ+ Students and Implications for School Counselors. Issue 3 (2nd August 2021) - Wikoff, Haley D.; Lane, Erin M. D.; Beck, Matthew J.
Abstract: Individuals who identify as gifted or LGBTQ + often have qualitatively different academic, social, and emotional experiences throughout their adolescent development. However, scant research exists exploring the development of individuals who hold these intersecting identities. Using an anonymous retrospective qualitative survey, 75 participants who identify as both gifted and LGBTQ + shared narratives about their development as gifted LGBTQ + students. Using interpretive phenomenological analysis, the data revealed three superordinate themes that articulated the overall description of the gifted LGBTQ + participants' development. Implications of the results for school counselors are provided.